Identification of Risks, Sustainability and Problems of Fuel Security of Ukraine and the Countries of the European Area (Matrix Approach) - Khaustova Viktoriia Ye.; Hubarieva Iryna O.; Salashenko Tetiana I.; Kostenko Dmytro M. (Problemi Ekonomiki)
Today, Ukraine has a critically low level of fuel security, which is associated with a drop in oil production, a decline in oil refining and limited opportunities to import oil and motor fuel. The aim of the study is to develop a methodical approach to assessing the fuel security of Ukraine and the countries of the European space, which involves the calculation of local indicators of fuel security by components and levels. It is proposed to assess the fuel security of Ukraine and European countries according to four security components: accessibility, availability, acceptability, affordability. A methodical approach to identifying problems in ensuring fuel security is proposed, which, unlike the existing ones, is based on a system of matrices for positioning Ukraine and the countries of the European space in the plane of coordinates: «Accessibility of crude hydrocarbons for indigenous production, in particular year – Accessibility of crude hydrocarbons for oil refining»; «Availability of crude hydrocarbons for oil refining – Availability of motor fuel for final consumption»; «Acceptability of crude oil as a feedstock for refining – Acceptability of motor fuel in oil refining feedstock»; «Affordability of crude hydrocarbons imports – Affordability of motor fuel imports». The analysis of the components and levels of fuel security of Ukraine and the countries of the European space made it possible to determine that the highest level of fuel security in 2021 had the following countries: Norway, Great Britain, Lithuania, Spain; the lowest level of fuel security had Montenegro, Slovenia, Latvia, Estonia. In 2021, Ukraine ranked 24th among 29 European countries in terms of fuel security that was 35%. The decrease in the level of fuel security of Ukraine was influenced by: the destruction of production facilities as result of russian military aggression, a reduction in production, and limited opportunities to import crude hydrocarbons. The key problems in ensuring Ukraine’s fuel security include: low level of accessibility of crude hydrocarbons for indigenous production and crude hydrocarbons for oil refining; low availability of crude hydrocarbons for oil refining and low availability of motor fuel for final consumption. To ensure fuel security, Ukraine needs to increase the production of crude hydrocarbons, increase the volume of oil refining for final consumption, and develop the production of synthetic motor fuel from coal.